Recent advances in energy efficient-QoS aware MAC protocols for wireless sensor networks - Muzakkari B.A.; Mohamed M.A.; Abdul Kadir M.F.; Mohamad Z.; Jamil N. (Accent Social and Welfare Society, 2023)
Wireless sensor networks (WSNs) is a distribution of several tiny, low-cost sensor nodes, wirelessly connected altogether for the purpose of monitoring physical or environmental conditions. Due to the vast interest for WSN, a rapid technological breakthrough has been observed in sensor elements such as processor, operating system, radio, and battery. From the perspective of seven layer approach, the medium access control (MAC) protocols are identified as the most crucial element, being responsible for coordinating communication amongst the sensor nodes. In addition, the functionality of the WSN MAC protocol has a subtle influence on parameters such as battery consumption, packet collision, network lifetime and latency. In this paper, we survey some of the most recent WSN contention-based, scheduling-based, and hybrid MAC protocols by focusing on their underlying principle, various advantages and limitations and their applications. Treating energy saving as the benchmark, further examining the directed towards the treatment of quality of service (QoS) performance metrics within these particular protocols. The result shows that the majority of the protocols leaned towards energy conservation with other parameters are either supported partially or traded off. Latency, throughput, bandwidth utilization, channel utilization is not considered in the design of most of the protocols. Indeed, the energy domain has gotten a vital breakthrough with the advent of other modes of energy saving such as energy harvesting techniques. However, other parameters such as latency, throughput, packet loss, network and bandwidth availability that comes under QoS metrics also play a critical role in future development of MAC protocols for WSNs. 2018 ACCENTS.